Bacillus subtilis Contributes to Amylase Production in the Honey Sac of Apis mellifera - Miao Wang; Wenzheng Zhao; Danyin Zhou; Jian Huang (Insects)
Background: Amylase activity is a critical biomarker for assessing the freshness of honey. Historically, bees have been considered the sole source of honey amylase. However, recent studies suggest that Bacillus subtilis may also contribute to amylase production in the honey sac of Apis mellifera. Methods: In this study, amylase levels were measured in samples of nectar, honey sac fluid, and honey. The identification of B. subtilis in nectar, honey sac, and honey was evaluated. An in vitro bacterial culture system and a feeding experiment were developed to simulate honey sac conditions. Results: Our results showed that B. subtilis was detected in all sample groups, with the highest concentration in honey sac samples. Amylase levels in honey sac and honey samples were significantly higher than those in nectar. In the simulation experiment, amylase activity was only observed in cultures containing both B. subtilis and sucrose/nectar; no activity was detected in cultures containing only H2O or no B. subtilis. In the feeding experiment, bees fed sucrose or nectar showed higher amylase activity in their honey sacs than those fed water. Conclusions: Our data show that B. subtilis can produce amylase and offer potential for more standardized quality assessment of honey.